2021
DOI: 10.25176/rfmh.v21i3.3520
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Of Coinfection By Respiratory Pathogens And Its Impact On The Prognosis Of Patients With COVID-19.

Abstract: Frecuencia de coinfección por patógenos respiratorios y su impacto en el pronóstico de pacientes con COVID-19. Rev. Fac. Med. Hum. Abril 2021; 21(2):610-622.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…Durante la pandemia por Covid-19, las coinfecciones por A. baumannii se relacionaron a infecciones bacterianas secundarias o sobreinfecciones, principalmente bacteriemias e infecciones del tracto urinario 8 . Así mismo, la coinfección del virus SARS-CoV-2 con bacterias, hongos incluso otros virus parece ligarse a una mayor frecuencia de desenlaces desfavorables 9 , para el caso de VSR, las coinfecciones más comunes reportadas son por Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae, Moraxella catarrhalis, Haemophilus influenzae y Klebsiella pneumoniae 10 . Sin embargo, no existen a la fecha reportes de coinfecciones tanto de S. marcescens o A. baumannii con VSR, a pesar de ello, existen mecanismos implicados en las coinfecciones y superinfecciones producidas por virusbacterias que pueden explicar este hallazgo.…”
Section: Discussionunclassified
“…Durante la pandemia por Covid-19, las coinfecciones por A. baumannii se relacionaron a infecciones bacterianas secundarias o sobreinfecciones, principalmente bacteriemias e infecciones del tracto urinario 8 . Así mismo, la coinfección del virus SARS-CoV-2 con bacterias, hongos incluso otros virus parece ligarse a una mayor frecuencia de desenlaces desfavorables 9 , para el caso de VSR, las coinfecciones más comunes reportadas son por Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae, Moraxella catarrhalis, Haemophilus influenzae y Klebsiella pneumoniae 10 . Sin embargo, no existen a la fecha reportes de coinfecciones tanto de S. marcescens o A. baumannii con VSR, a pesar de ello, existen mecanismos implicados en las coinfecciones y superinfecciones producidas por virusbacterias que pueden explicar este hallazgo.…”
Section: Discussionunclassified
“…Coinfections with microbial pathogens have played an important role in increasing the morbidity and mortality rate in pandemics, and SARS-CoV-2 is no exception [ 38 ]. Coinfection between other microorganisms and this new coronavirus is an important factor to take into account in COVID-19, as it may increase the difficulties in diagnosis, management, and prognosis, and even worsen symptoms and mortality [ 12 ]. It should be noted that a wide spectrum of atypical presentations were found to be associated with COVID-19, which complicated critically ill immunocompromised patients [ 39 ].…”
Section: Coinfections Associated With Sars-cov-2 In Colombiamentioning
confidence: 99%
“…In a study conducted in Colombia, a high incidence of early mortality associated with COVID-19 24 h after hospital admission was reported [ 11 ]. However, studies related to the incidence of coinfection and superinfection in patients with COVID-19 are generally limited, especially in Latin American countries [ 5 , 12 , 13 ]. It was observed that severely ill COVID-19 patients, especially those in the intensive care unit (ICU), were more prone to secondary infections, owing to the increased use of prophylactic or therapeutic antibiotics whose task is to ensure the successful eradication of susceptible pathogens [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, en la coinfección adquirida en la comunidad en el momento del diagnóstico de COVID-19, los agentes bacterianos más frecuentes fueron principalmente Streptococcus pneumoniae y S. aureus (36). Estas bacterias juegan un rol importante en la mortalidad y complicaciones en el curso de la COVID-19, por lo que se recomienda, en pacientes graves, el uso de antibioterapia empírica ante una mala evolución clínica (37).…”
Section: Coinfecciones Bacterianasunclassified